2011
DOI: 10.1007/s00534-011-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic study and meta‐analysis of C‐reactive protein as a predictor of postoperative inflammatory complications after pancreatic surgery

Abstract: According to this limited evidence, CRP levels had a low to moderate diagnostic accuracy. Large, blinded studies are warranted for a more precise estimation of CRP's diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 51 publications
1
25
0
2
Order By: Relevance
“…Trotzdem ist die Ausbildung einer klinisch apparenten Cholangitis eine eher seltene Komplikation und tritt meist nur bei einer Behinderung des Galleflusses auf. Ihre Häufig-keit wird in Abhängigkeit vom operativen Eingriff mit 1-10 % nach Pankreaseingriffen und 17-60 % nach Lebertransplantation angegeben [33, 53,63]. Die eindeutige Diagnose einer postoperativen Cholangitis ist im intensivmedizinischen Setting häufig schwierig.…”
Section: Postoperative Cholangitisunclassified
“…Trotzdem ist die Ausbildung einer klinisch apparenten Cholangitis eine eher seltene Komplikation und tritt meist nur bei einer Behinderung des Galleflusses auf. Ihre Häufig-keit wird in Abhängigkeit vom operativen Eingriff mit 1-10 % nach Pankreaseingriffen und 17-60 % nach Lebertransplantation angegeben [33, 53,63]. Die eindeutige Diagnose einer postoperativen Cholangitis ist im intensivmedizinischen Setting häufig schwierig.…”
Section: Postoperative Cholangitisunclassified
“…The authors suggested an algorithm with early CT scan on 4th postoperative day based on CRP value. In 2012, Warschkow et al [22] similarly analyzed CRP value in prediction of global IPC on a series of 280 pancreatic surgical procedures including PD, left pancreatectomy, total pancreatectomy and cystojejunostomy; in their experience, IPC prevalence was equal to 54.6%, but CRP did not appear capable of predicting IPC development with adequate accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CRP appears in our experience to be a helpful tool in clinical practice, even if its use should be rationalized, since CRP predictive power for septic complications is not uniform during the overall postoperative course [22,23,25]. In the first 2 postoperative days, the physiologic response to surgical stress hides the effects on CRP levels of an ongoing septic process, making its assay useless and, moreover, generating a small but unjustified extra cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations